Increasing Repurchase Interest Through Improving Product Quality: An Analysis of Garut Sheep Sales at PT Bima Sakti Tigaroot - Rusdian, Suca; Ameliani, Meli (Manunggal Halim Jaya, 2024)
Companies in the livestock sector face great challenges in increasing consumer repurchase interest, especially in the midst of increasingly fierce competition. This study aims to analyse the effect of product quality on consumer repurchase intention at PT Bima Sakti Tigaroot, a company engaged in the sale of Garut sheep. This type of research is quantitative with descriptive and associative approaches. The study population consisted of 55 regular customers of the company, and the sampling technique used was a census, where the entire population was sampled. The research was conducted at PT Bima Sakti Tigaroot, with a research duration of several months. The results showed that product quality has a significant influence on consumer repurchase intention. The better the product quality, the more likely consumers are to repurchase. The implication of this research is the importance of companies to focus on improving product quality, especially the physical and health aspects of sheep, in order to increase customer loyalty and higher sales volume.